Thinking about post-pandemic architecture: Heidegger, Japanese new wave and new Dutch architecture - Jordan Shishovski (University American College Skopje, 2021)
Whether we are embracing or countering technology, we are unable to avoid its grip on our world. Architecture is one of the areas which are the most indebted to technology. The most influential thinker on technology and contemporary architectural theory is Martin Heidegger. According to him technology is not controlled by humanity, but on the contrary: humanity is subjected to the will to power of technology as a way of revealing of Being. It conceals all other possibilities for revealing, such as the poetic way. This for Heidegger is the greatest Danger of technology since it opens the doors to nihilism. COVID-19 pandemic further pushes the cold rationale of the calculative thinking underlying technology, especially in the redesigning of our built environment. This crisis actually threatens to accelerate the dominance of the essence of technology which he calls the enframing (Gestell), and brings the greatest Danger to its full closure of all other ways of revealing of Being once and for all! This paper aims at thinking on Heidegger's notion of the 'appropriating event' (Ereignis), through 'letting-be" (Gelassenheit) for opening alternative paths of architectural design by gaining a free relationship to technology. Concrete examples from architectural design and theory of the Japanese 'New Wave' architecture, and architects such as Kurokawa Kisho, as well as contemporary Dutch architecture - MVRDV and Rem Koolhaas' OMA, will be discussed as examples for their double move towards technology: their full embracement of the latest technologies in their design and building, while explicitly rejecting the underlying technological rationality and calculative thinking associated with technology.
Keywords: 330; COVID-19; technology; architecture; Heidegger; Kurokawa; Koolhaas; MVRDV